Implementation of Graph Theory on the Setting of the Traffic Light Intersection - Iis Isnaeni; Siti Rahmah; Uke Agosa (ITEJ (Information Technology Engineering Journals), 2021)
On the crossroads of course required setting traffic lights for vehicles that can be flashed with a sense of security and comfort. The duration of the traffic lights can be set to the maximum extent possible so that the vehicle could pass the road regularly. There are many solutions to manage traffic at a crossroads. One of them is a solution which will be given through this observation. This paper aims to describe the related optimization settings traffic by using the algorithm staining which aims to get the chromatic number of graphs. The optimization needs to be done due to the settings of the traffic at the Intersection of Palimanan often seen traffic jams and crowded at rush hour as a result of policies that allow the current to be incompatible. The application of the algorithm staining Welch – Powel to determine the chromatic number of graphs can be another option to resolve the problem. After the current – the current at the traffic being transformed into a graph model that will be coloring a graph and calculating the number lens. Chromatic number of the graph model is 4 so there is a change in the duration of the red and green lights on the traffic. Although there is a reduction in the duration of the red light and the addition of the duration of the green light, the removal of the current incompatibility can minimize the possibility of congestion.